Effects of functional CYP2C8, CYP2C9, CYP3A5, and ABCB1 genetic variants on the pharmacokinetics of insulin sensitizer pioglitazone in Chinese Han individuals. Issue 4 (April 2017) - Yin, Sheng-Ju; Qi, Hui-Min; Wang, Xin; Zhang, Pu; Lu, Yuan; Wei, Min-Ji; Li, Pu; Qi, Guang-Zhao; Lou, Ya-Qing; Lu, Chuang; Zhang, Guo-Liang
Abstract : Background and objectives: Pioglitazone is a thiazolidinedione antihyperglycemic drug with insulin-sensitizing properties. We investigated whether the variant genotypes of cytochrome P450 2C8 ( CYP2C8 ), CYP2C9, CYP3A5 and transporter ABCB1 influence the pharmacokinetic phenotype of the substrate pioglitazone in Chinese individuals. Participants and methods: Single-nucleotide polymorphisms were determined by the PCR-restriction fragment length polymorphism method in 244 ( CYP2C8 and CYP2C9 ) healthy Chinese Han individuals. After a single oral dose of 30 mg pioglitazone, the plasma concentrations of the parent drug and of two major active metabolites M-III and M-IV were measured using a validated LC-MS/MS in 21 (genotyping CYP3A5 and ABCB1 ) of these 244 volunteers. Results: The results confirmed that the unique frequencies of CYP2C8 * 2 (0.0%), CYP2C8 * 3 (0.0%), and CYP2C9 * 2 (0.0%) alleles were significantly different from those reported in Whites and Africans, and there were only 10 variant CYP2C9 * 1/ * 3 heterozygous ( CYP2C9 * 3 carriers) among 244 Chinese individuals. These results were similar to those reported in Asian ethnic populations, including the Chinese. Unexpectedly, the pioglitazone AUC0–48 in CYP2C9 * 3 carriers was lower (50.8%), whereas the AUC0–48 ratios of metabolites M-III/pioglitazone and M-IV/pioglitazone increased to 134.3 and 155.8%, respectively, compared with the wild-type CYP2C9 * 1/ * 1 homozygous. Moreover, this phenomenon was not observed in individuals with genetic variants of CYP3A5 * 3 and ABCB1 ( C1236T ). Conclusion: The present research suggests that the CYP2C8, CYP3A5, and ABCB1 genes play no significant role in the interindividual variation of pioglitazone pharmacokinetics, whereas CYP2C9 * 3 carriers are likely to accelerate the metabolism of this antidiabetic drug in the Chinese Han ethnic population. Abstract : Supplemental Digital Content is available in the text.